Physiological and biochemical characteristics and identification of actinomycete strains isolated from soil samples in Hanoi - Nguyen, Thanh Chung; Nguyen, Thi Huong; Nguyen, Thi Ngoc Anh; Dang, Bao Son; Nguyen, Ngoc Oanh (Vietnam Journal of Biotechnology, 2025)
Actinomycetes are a rich source of natural compounds with diverse biological activities. In this study, the actinomycete strain Streptomyces sp. CH8.1 was identified as Streptomyces virginiae through 16S rDNA sequence analysis, alongside the determination of its physiological and biochemical characteristics. Strain CH8.1 demonstrated robust growth on media typical for actinomycetes and could utilize most common nitrogen and carbon sources, including sucrose, maltose, lactose, mannitol, galactose, xylose, cellobiose, glycerin, raffinose, tyrosine, tryptone, peptone, and certain ammonium salts. CH8.1 exhibited antimicrobial activity against both Gram-positive and Gram-negative bacteria, including Staphylococcus aureus CCARM 3640 (MIC of 32 µg/mL), Salmonella enterica ATCC 14028 (MIC of 16 µg/mL), Kocuria rhizophila NBRC 12708 (MIC of 32 µg/mL), Bacillus subtilis VTCC 6633 (MIC of 8 µg/mL), Escherichia coli ATCC 25922 (MIC of 32 µg/mL), and Vibrio sp. (MIC of 16 µg/mL). The R2YE medium was identified as the most suitable for producing antimicrobial compounds. And the CH8.1 strain was demonstrated to contain the type II PKS gene cluster, while lacking the type I PKS gene cluster.